Simulation of Emergency Training for Nursing Students - Reis, Renata Karina; Melo, Elizabete Santos; Costa, Christefany Régia Braz (Revista Cuidarte, 2020)
Introduction: Training nursing students in cardiopulmonary resuscitation (CPR) maneuvers is essential for safe and quality performance in different nursing performance scenarios. CPR integration into clinical practice settings, from the early years of the degree, provides greater confidence when performing it in emergency situations. The study aimed to evaluate the knowledge of newly graduated nursing students before and after receiving Basic Life Support (BLS) training through simulation. Materials and Methods: A quasi-experimental study was conducted at a public higher education institution in southeastern Brazil in 2015. The students answered a pre-test and, right after the intervention, answered a post-test. For the analysis, the McNemar and Wilcoxon paired tests were used. Results: Students were identified as having satisfactory knowledge (≥ 80%) on several subjects immediately after taking the course. However, the test questions related to the links in the chain of survival (-18.7%; p = 0.004) and to the steps of open airway maneuver (-16.0%; p = 0.091) indicated a reduction in the number of correct answers after the intervention. Discussion: The use of combined strategies, including the medium-fidelity simulation for teaching BLS, has facilitated the understanding of BLS content. Conclusions: The use of simulation showed a positive evolution of knowledge related to the depth of chest compression, the sequence of CPR steps and the compression-ventilation ratio for CPR per minute.Como citar este artigo: Costa, Christefany Régia Braz; Melo, Elizabete Santos; Reis, Renata Karina. Simulação no ensino de emergência para estudantes de enfermagem. Revista Cuidarte. 2020; 11(2): e853. http://dx.doi.org/10.15649/cuidarte.853
Keywords: Simulation Training; Cardiopulmonary Resuscitation; Nursing, Students; Nursing, Education.; Nursing